Habitat needs of cetaceans in the North-East Atlantic in relation to human pressures and their management - Mendão, Vera Isabel Marques (2009)
Tese de mestrado, Ecologia Marinha, 2009, Universidade de Lisboa, Faculdade de Ciências Resumo alargado em português disponível no documento Cetaceans are very complex in their biology and ecology, having particular habitat needs that influence their global and local distribution, such as oceanographic features and prey availability. Knowledge on specific habitat needs (essential environmental characteristics for the animals' survival) is of major importance for the definition of effective conservation goals and management measures. These species are vulnerable to pressures from human activities, for instance from whaling, fisheries and navigation, as well as those releasing contaminants or generating oceanic noise. The available information on cetacean habitat preferences and registered human activities impacts was compiled for North-East Atlantic cetaceans, from primary and secondary references, as presence/absence data matrices. These were analysed descriptively and through Correspondence and Classification Analyses. The habitat needs analyses produced a clear distinction between mysticetes (baleen whales) and odontocetes (toothed whales), and, in a less obvious way, two trends in the dispersion of the odontocetes. The characteristics influencing these distinctions were mainly related to feeding preferences, typical group size, reproductive seasonality and migratory patterns. Similarly, the human activities analysis showed the distinction between mysticetes and odontocetes, and among these, between beaked and sperm whales, and dolphins. Mysticetes were found to be mainly affected by whaling and noise from shipping; beaked and sperm whales by noise from seismic surveys and military activities; and dolphins by by-catch, whale-watching and collisions with ships. Given the increase of human impacts on marine ecosystems, several international, European, regional and local agreements and legislation have been agreed. In general, these aim to reduce and monitor human pressures on biodiversity, and they ...